POTENSI DAN KARAKTERISTIK LIMBAH PEMBALAKAN PADA PT KEMAKMURAN BERKAH TIMBER PROVINSI KALIMANTAN TIMUR - Soenarno (BRIN Publishing, 2014)
Despite logging activity has been carried out carefully, the logging waste remains difficult to avoid. Occurrence of logging waste is caused by natural factors (hole, crooked, rotten pith, notch) and technical factors (splits and other felling faults). Individual logging waste at natural forest concession of PT Kemakmuran Berkah Timber ranged from 0.577 to 0.728 m³/tree with an average of 0.677 m³/tree. The waste of stump (0.006 m³/tree), 0.325 m³/tree), and in top (0.355 m³/tree). In regard with wood quality, 0.378 m³/tree (± 55.85%) of them can be categorized as “good”, and the remaining 0.299 m³/tree (± 44.15%) is classfied as “defect”, continuing notch, bent, broken or holes. Potency and charactertic of logging wastes differ among Red Meranti (Shorea spp.), Kapur (Dryobalanops spp.) and Majau (S. johorensis). For Red Meranti, the butt waste were greater (0.623 m³/tree or 64.94%) than the top waste (0.322 m³/tree or 34.17%) and the stump waste (0.009 m³/tree or 1.00%). Kapur (Dryobalanops spp.) and Majau (S. johorensis), top waste than the butt and stump wastes volume of Kapur have greater is 0.356 m³/tree (81.63%), with butt waste of 0.076 m³/tree (17.51%) and stump waste of 0.004 m³/tree (0.86%). The logging wastes of Majau were 0.385 m³/tree (59.42%); 0.257 m³/tree (39.72%), and 0.006 m³/tree (0.86%), for the top, butt and stump respectively.